answersLogoWhite

0


Best Answer

98a + 5 + 6a = 104a + 5

User Avatar

Wiki User

14y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: Simplify98a plus 5 plus 6a
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Factor 36a2-60a plus 25?

36a2 - 60a + 25 = 36a2 - 30a - 30a + 25 = 6a(6a - 5) - 5(6a - 5) = (6a - 5)(6a - 5) = (6a - 5)2


3(6a plus 5) plus 30?

3(6a + 5) + 30 18a + 15 + 30 18a + 45


5a plus 5 equals 6a-7 equals?

To solve the equation 5a + 5 = 6a - 7, you first want to simplify both sides. Start by combining like terms on each side of the equation. Add 7 to both sides to isolate the variable terms on one side. Then, subtract 5a from both sides to solve for the variable a. The final answer is a = 12.


How do you solve a plus 6a-a equals 30?

36


Factorise 6a-12b plus 30?

6a -12b + 30 = 6 (a - 2b + 5)


3a plus 2 plus 3a-5?

6a-3


6a plus 4 when a equals 5?

34


How do you find the sum or difference of (5a2 plus 6a plus 2)-(7a2-7a plus 5)?

Combine like terms, adding/subtracting the coefficients: (5a² + 6a + 2) + (7a² - 7a + 5) = (5+7)a² + (6-7)a + (2+5) = 12a² - a + 7 (5a² + 6a + 2) - (7a² - 7a + 5) = (5a² + 6a + 2) + (-7a² + 7a - 5) = (5-7)a² + (6+7)a + (2-5) = -2a² + 13a - 3


2a-4b plus 4b-6a equals a plus b?

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1


What is 24ab - 42ax - 20b plus 35x factored?

24ab - 42ax - 20b + 35x = 6a(4b - 7x) - 5(4b - 7x) = (4b - 7x)(6a - 5)


What is 6a-13 equals -5?

6a - 13 = -5 Therefore, 6a = 8 a = 8/6 a = 1.3 recurring (that is, 1.3333..)


When 3a2-2a plus 5 subtracted by a2 plus a equals 1?

Not sure why it is 3a2- if you mean 3*a*2, then: 3*a*2=6a (6a-2a)+5-2(a (or a2)+a)=1 4a+5-(2a+a)=1 4a+5-2a-a=1 Then take the 5 over (remember, the +5 become -5 when transposed): 4a-2a-a=1-5 Solving the equations on both sides gives: a=-4 Is this your answer?